2005
DOI: 10.1007/s00330-005-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

The value of magnetic resonance imaging for the diagnosis of arrhythmogenic right ventricular cardiomyopathy

Abstract: This study evaluated the diagnostic significance of a magnetic resonance imaging (MRI) based scoring model for identification of arrhythmogenic right ventricular cardiomyopathy (ARVC) in patients with MRI evidence of RV abnormalities. Fifty-three patients with RV myocardial abnormalities on MRI were divided into a group with ARVC 1 (n=17) and a group with other RV arrhythmias (n=37). Decision tree learning (DTL) and linear classification (based on a modified ARVC scoring model of major and minor criteria) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
3
17
1
Order By: Relevance
“…An interesting finding was that an increase in the presence of myocardial fatty replacement was not significantly related to the patients' BMI. This differs from previous reports by Maskimovic and Imada which showed that obesity is significantly more common in cases of fatty replacement of RV [14,22].…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…An interesting finding was that an increase in the presence of myocardial fatty replacement was not significantly related to the patients' BMI. This differs from previous reports by Maskimovic and Imada which showed that obesity is significantly more common in cases of fatty replacement of RV [14,22].…”
Section: Discussioncontrasting
confidence: 84%
“…We found that the presence of fat was associated with advanced patient age, a correlation also described by Fontarilan and Maksimovic [14,19]. A significant limitation of this work is that the Fig.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The condition, ARVC, has been diagnosed as involving fat deposits in the inter-ventricular septum, moderator band, or right ventricular wall, as well the enlargement of the right ventricle (RV); this diagnosis has often been performed by magnetic resonance imaging (MRI) or computed tomography (CT) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…CMR is able to obtain three-dimensional images to depict structural and functional abnormalities and so is well suited to demonstrate regional wall motion abnormalities, thinning and aneurysmal changes in the RV free wall, 23 increased RV and LV volumes, and increased T1 myocardial signal suggesting fatty infiltration. The role of LGE is currently being evaluated in this condition.…”
Section: W19mentioning
confidence: 99%